How to solve by quadratic formula: (p-q)x+(2q)/x=(p+q) ?
1 Answer
Nov 21, 2017
Explanation:
Given:
(p-q)x + (2q)/x = (p+q)
Multiply both sides of the equation by
(p-q)x^2+2q = (p+q)x
Subtract
(p-q)x^2-(p+q)x+2q = 0
This is in standard form:
ax^2+bx+c = 0
with
It has roots given by the quadratic formula:
x = (-b+-sqrt(b^2-4ac))/(2a)
color(white)(x) = ((p+q)+-sqrt((-(p+q))^2-4(p-q)(2q)))/(2(p-q))
color(white)(x) = ((p+q)+-sqrt((p^2+2pq+q^2)-(8pq-8q^2)))/(2(p-q))
color(white)(x) = ((p+q)+-sqrt(p^2-6pq+9q^2))/(2(p-q))
color(white)(x) = ((p+q)+-sqrt((p-3q)^2))/(2(p-q))
color(white)(x) = ((p+q)+-(p-3q))/(2(p-q))
That is:
x = ((p+q)+(p-3q))/(2(p-q)) = (2p-2q)/(2p-2q) = 1
or:
x = ((p+q)-(p-3q))/(2(p-q)) = (4q)/(2(p-q)) = (2q)/(p-q)